2011
DOI: 10.22436/jmcs.002.02.14
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Model Identification For Intelligent Control Of A Vehicle Speed Limit

Abstract: The need to increase road safety is a major concern, with millions of road users and pedestrians being killed in traffic accidents each year. Static speed limit signs are conventionally used to assist motorists in safe selection of speeds. Although appropriate to use under near ideal conditions, such signs fail to provide accurate information on speed selection when traffic and environmental conditions are less than ideal. To develop a variable speed limit system that utilizes fuzzy control technology to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, Hardy Santosa S and Agus Harjoko in their research used the Euclidean distance method to estimate vehicle speed and stated that the results of speed estimation from processing video data are still better than using speed gun with the highest accuracy rate of 90.5%. Other studies, Fuzzy approaches have also been used for speed estimation [26], [27].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, Hardy Santosa S and Agus Harjoko in their research used the Euclidean distance method to estimate vehicle speed and stated that the results of speed estimation from processing video data are still better than using speed gun with the highest accuracy rate of 90.5%. Other studies, Fuzzy approaches have also been used for speed estimation [26], [27].…”
Section: Related Workmentioning
confidence: 99%
“…FL has been applied in numerous application domains, including driver behaviour analysis. [41] presented a vehicle speed limit model, with a road safety model discussion based on fuzzy rules. A recent review paper has shown the relevance of FL for driving style analysis [25].…”
Section: State Of the Artmentioning
confidence: 99%